Increased Co-Expression of PD-L1 and CTLA-4 Predicts Poor Overall Survival in Patients with Acute Myeloid Leukemia Following Allogeneic Hematopoietic Stem Cell Transplantation - Chen C; Qiu K; Chen J; Wang S; Zhang Y; Wang C; Li Y (ImmunoTargets and Therapy)
Cunte Chen,1,2,* Kangjie Qiu,2,* Jie Chen,3,* Shunqing Wang,1 Yuping Zhang,1 Caixia Wang,1 Yangqiu Li2 1Department of Hematology, Guangzhou First People’s Hospital, Institute of Blood Transfusion and Hematology, Guangzhou Medical University, Guangzhou, 510180, People’s Republic of China; 2Institute of Hematology, School of Medicine, Key Laboratory for Regenerative Medicine of Ministry of Education, Jinan University, Guangzhou, People’s Republic of China; 3Department of Hematology, First Affiliated Hospital, Jinan University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yangqiu Li, Institute of Hematology, School of Medicine, Key Laboratory for Regenerative Medicine of Ministry of Education, Jinan University, Guangzhou, 510632, People’s Republic of China, Email yangqiuli@hotmail.com Caixia Wang, Department of Hematology, Guangzhou First People’s Hospital, Institute of Blood Transfusion and Hematology, Guangzhou Medical University, Guangzhou, 510180, People’s Republic of China, Email wangcx225@163.comPurpose: Our previous study has demonstrated that high expression of immune checkpoints (ICs) was significantly associated with adverse clinical outcomes in patients with acute myeloid leukemia (AML). This study aims to investigate the significance of the alteration of IC co-expression for evaluating the prognosis of AML patients following allogeneic hematopoietic stem cell transplantation (allo-HSCT).Patients and Methods: Quantitative real-time PCR (qRT-PCR) data of bone marrow (BM) samples from 62 de novo AML patients, including 37 patients who received allo-HSCT and 25 patients who received chemotherapy only, were used for prognostic analysis.Results: High expression of PD-1, PD-L1, PD-L2, CTLA-4, and LAG-3 was associated with poor overall survival (OS) in AML patients receiving allo-HSCT, while the expression levels of PD-1, PD-L2, CTLA-4, and LAG-3, other than PD-L1, were not significantly correlated with OS in AML patients receiving chemotherapy. Importantly, PD-L1/CTLA-4 was the best combination model for predicting poor OS in AML patients following allo-HSCT, especially combined with minimal residual disease (MRD).Conclusion: High expression of ICs in BM of AML patients following allo-HSCT was related to poor outcomes, and increasing co-expression of PD-L1 and CTLA-4 might be one of the best immune biomarkers to predict outcomes in patients with AML.Keywords: acute myeloid leukemia, allo-HSCT, immune checkpoint, biomarker, prognosis